Recent Progress in Coordination Chemistry - Peter Segľa; Ján Pavlik (Inorganics, 2023)
The following Special Issue of Inorganics is based on the discussions initiated at the International Conference on Coordination and Bioinorganic Chemistry (ICCBIC), which has been organized and held biennially since 1964 [...]